Pengetahuan Petani dalam Budidaya Tanaman Nilam di Desa Laworo Kecamatan Tiworo Kepulauan Kabupaten Muna Barat - Rosnini, Wa Ode Sitti; Hamzah, Awaluddin; Salahuddin, Salahuddin; Buana, Tjandra (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
This study aims to determine the Knowledge of Farmers in Patchouli Cultivation in Laworo Village, Tiworo Islands, West Muna Regency. The location selection used in this study was determine intentionally or purposively. The time of this research was carried out in December 2021 to January 2022. Data analysis used in this study using the class interval formula. The population in this study were all patchouli farmers in Laworo Village as many as 19 people. The data analysis used is quantitative data using the class interval formula. The results showed that in general most of the farmers in Laworo Village had a high level of knowledge in patchouli cultivation, namely land processing 68,42 %, planting 100%, maintaining 64,29%, and harvesting 73,68%, but thereare some farmers in the nursery knowledge are in the medium category that is 63,15%.